Microbial (E)-4-hydroxy-3-methylbut-2-enyl pyrophosphate reductase (IspH) and its biotechnological potential: A mini review - Huang, Shiyong; Xue, Yanfen; Ma, Yanhe; Zhou, Cheng (Frontiers in Bioengineering and Biotechnology, 2022)
(E)-4-hydroxy-3-methylbut-2-enyl pyrophosphate (HMBPP) reductase (IspH) is a [4Fe-4S] cluster-containing enzyme, involved in isoprenoid biosynthesis as the final enzyme of the methylerythritol phosphate (MEP) pathway found in many bacteria and malaria parasites. In recent years, many studies have revealed that isoprenoid compounds are an alternative to petroleum-derived fuels. Thus, ecofriendly methods harnessing the methylerythritol phosphate pathway in microbes to synthesize isoprenoid compounds and IspH itself have received notable attention from researchers. In addition to its applications in the field of biosynthesis, IspH is considered to be an attractive drug target for infectious diseases such as malaria and tuberculosis due to its survivability in most pathogenic bacterium and its absence in humans. In this mini-review, we summarize previous reports that have systematically illuminated the fundamental and structural properties, substrate binding and catalysis, proposed catalytic mechanism, and novel catalytic activities of IspH. Potential bioengineering and biotechnological applications of IspH are also discussed.